Analysis of the Bioactive Compounds N-Hexane Extract of Ramie Leaves and Flowers (Boehmeria nivea) and Antibacterial Test Against Escherichia coli and Klebsiella pneumoniae (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2022)
Ramie (Boehmeria nivea) is one of the Urticaceae family plants with various potential for pharmacological development. In this study, we analyzed the bioactive content of the n-hexane extract of B. nivea leaves and flowers, and the crude extract was tested for antibacterial activity. The metabolites in the leaves and flowers of ramie were analyzed using a Gas Chromatography-Mass Spectrometer (GC-MS). Antibacterial potential analysis was carried out by disc diffusion method using n-hexane extract of ramie leaves and flowers at concentrations of 20%, 40%, 60%, 80%, and 100% in inhibiting Escherichia coli and Klebsiella pneumoniae. Antibacterial potential was observed based on the average result of three observations of the diameter of the clear zone to determine the effectiveness of the extract. The results showed that the metabolome data of the n-hexane extract of ramie leaves were obtained as many as 40 compounds. Meanwhile, ramie flower metabolome analysis obtained 47 compounds, but one compound has not been identified. The crude n-hexane extract of B. nivea flower gave antibacterial activity at 80% and 100% concentrations against E. coli with an average clear zone of 9.15 ± 0.31 mm and 10.29 ± 0.28 mm. In contrast, the n-hexane extract of B .nivea leaves did not show any antibacterial activity. The results of confirmation of the dominant compound by GC-MS showed that the n-hexane extract consisted of tetratetracontane, tetracontane, Stigmast-5-en-3-ol,(3.beta.,24S)-(CAS)Clionasterol, methyl commate D, and 2,6,10,14,18,22-Tetracosahexsaene,2,6,10,15,19,23-hexamethyl-, (all-E). The n-hexane extract of B. nivea is recommended for other potential biological activities, such as anti-inflammatory, antioxidant, and analgesic.